Particle size impact on pyrolysis of multi-biomass: a solid-state reaction modeling study - Sabah Mariyam (14150859) (2023)
yrolysis has gained significant attention due to its generation of value-added products from waste feeds in an environmentally friendly manner. The primary purpose of this study is to understand the effect of different particle sizes of biomass wastes – date stones (DS), cow manure (CM), and spent coffee grounds (SCG) – to understand better and design a biomass pyrolysis system. Thermogravimetric analysis of four different sizes of DS, SCG, and CM (range 1 mm to 125 μm) and a mixed sample (for each feed) was conducted at a heating rate of 10K/min from room temperature to 1173.15 K at inert conditions and employed model-based Coats–Redfern equations to understand the kinetic and thermodynamic parameters of the pyrolysis process. All the particle sizes except 355–125 μm for DS and SCG have the best-fit reaction mechanism of Ginstling-Brounshtein (D4). Both activation energy and pre-exponential factor decreased from 18.78 to 5.57 kJ/mol and 1.16 E+10 to 1.48 E+08 with reducing particle sizes. The onset degradation temperature, activation energy, change in enthalpy, and entropy decrease with particle sizes. The product formation is favored for all feeds and particle sizes, as the difference between the enthalpy and activation energies (Ea) is below 10 kJ/mol. As a result of their substantially lower activation energies and better reaction thermodynamics, mixed and smaller particle-sized biomass are favored. Other Information Published in: Energy Sources, Part A: Recovery, Utilization, and Environmental Effects License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/15567036.2023.2196945